Economic Evaluation of Housing Subsidy Systems : A Methodology with Application to Morocco - le Blanc, David (World Bank, Washington, DC, 2012)
Most countries do not use one single type of housing subsidy but combine many of them. The author provides operational criteria that allow evaluation of systems of housing subsidies, both at the individual program level and at the aggregate (country) level. The author examines the public finance assessment criteria used by different authors to analyze subsidy programs and confront them systematically. The author ends up with a map of criteria, which covers the range of topics interesting to policymakers. For each criterion, the author tries to provide empirical measures that can be retrieved from existing programs. The author then provides an aggregation method allowing a synthesis of diagnoses about the quality of the housing subsidies system at the country level. The aggregation technique offers a simple way to visualize the main features of a subsidy system, as well as the effects on the system of reforms or improvements of particular programs. The author applies the methodology to the system prevailing in Morocco in 1995 and 2004. The analysis shows that the most visible subsidies might not have been the most inefficient, nor the most resource consuming for the state. Examination of policy changes since 1995 shows that while the most visible subsidies received nearly all the government's attention, large invisible subsidies remain at the heart of Morocco's housing policy. The framework used here is very general and can be used to compare the Moroccan system with those of similar countries.